Pola Asuh Otoritatif Untuk Membentuk Karakter Anak - Ni Luh Ika Windayani; Komang Teguh Hendra Putra (STAHN Mpu Kuturan Singaraja, 2021)
The development of this era is so rapid that parents are not only intellectually intelligent but also have character to shape the character of their children. Character is learned by children through modeling the family members around them, especially the parents. The behavior of parents will be imitated directly or indirectly then will be studied and imitated by children. Therefore, the importance of the right parenting style to create a child with character is really crucial. There are three parenting styles, namely (1) Authoritarian parenting, in which parents make unilateral rules that must be obeyed by children regardless of whether the child likes it or not. (2) Permissive parenting is giving full freedom to children to do what they like. (3) Authoritative parenting is a parenting pattern that gives children the freedom to do something, but is still under the supervision, control, and guidance of their parents. Of the three parenting styles, authoritative parenting is the ideal parenting style. The application of authoritative parenting has a positive impact on the development of children in the future because children are always trained to make decisions and are ready to accept all the consequences of the decisions taken. Thus the potential of the child can develop optimally, because the child performs all activities according to his will and potential. While parents provide control and guidance when children do negative things that can damage the child's personality.